Marketing digital y posicionamiento en la empresa Yoly Motor's EIRL, Chepén 2021 - León Millones, Karen Jacqueline (2022)
The purpose of the research was to determine the relationship between digital marketing and positioning in the company Yoly Motor's EIRL, Chepén. Applied type study with non-experimental design and correlational level; with a sample of 30 customers of Yoly Motor's EIRL company; Two questionnaires were used as instruments, one for digital marketing and the other for positioning. The results were processed with descriptive and inferential statistics, using the Excel 2019 program and the SPSS v 26 statistical package to identify the correlation between the variables under study, the main result was that Spearman's Rho = 0.863, finding a positive correlation and significant, with significance = 0.000 less than 5%; concluding that if the company makes use of strategies related to digital marketing in the different social networks or digital platforms, then it will have adequate publicity for its brand and thus raise the brand's memory in the consumer's mind, creating a loyalty of this and a genuine and efficient positioning.